Design, synthesis and biological evaluation of acridone glycosides as selective BChE inhibitors. (May 2020) - Ma, Weiwei; Bi, Jingjing; Zhao, Chuanfang; Gao, Yangguang; Zhang, Guisheng
Abstract: Based on structure analyses of butyrylcholinesterase (BChE), a series of 21 acridone glycosides were designed, synthesized and evaluated in vitro for their BChE and acetylcholinesterase (AChE) inhibitory activities. d -ribose derivative 6f exhibited the greatest inhibitory activity on BChE (IC50  = 6.95 μM), and was the most selective inhibitor of BChE with the IC50 ratio of AChE/BChE was 20.59. d -glucose and d -galactose derivatives 6a and 6b showed inhibitory activities against both AChE and BChE. Moreover, compounds 6a, 6b, 6f and 5t were found nontoxic on SHSY5Y neuroblastoma and HepG2 cell and exhibited remarkable neuroprotective activity. Besides, compound 6f showed mixed-type inhibition against BChE (Ki  = 1.76 μM), which renders 6f a potential agent for the treatment of Alzheimer's disease. These novel acridone hybrids might be used as efficient probes to reveal the relationship between ligands and BChE and pave the way for developing selective BChE inhibitors to further study the pathogenesis of alzheimer's disease. Graphical abstract: Image 1 Highlights: Novel acridone-carbohydrate hybrids were designed and synthesized efficiently. These compounds showed high inhibitory potency against AChE and BChE. D -ribose derivative 6f was the most selective inhibitors of BChE (IC50 6.95 μM) . They had no obvious cytotoxicity and exhibited effective neuroprotective activity.